Cruces de ganado de doble propósito en la Costa Atlántica colombiana: 1. Peso corporal hasta los 18 meses - Hernández B., Gustavo; Alvarado A., Leonardo; Carvajal R., Guillermo (Instituto Colombiano Agropecuario - ICA, 2019)
The Bos taitru.v-Bos mucus crossbreeding is the best genetic strategy for dual purpose systems of production in the tropics, so it is very important to compare several breeding groups for every productive trait. The purpose of the work was to study the growth rate of 10 breed groups in north western Colombia. The calves were raised under the dual purpose system, which include the permanency of the calves with their dams for 8 to 9 hours after partial milking of the cows. The data were analyzed by least squares methods and the means were compared by Tukey test. The analysis of variance revealed that breed group effect were significant for the 5 variables studied. At weaning the Zebu breed with 157.4 kg excelled all other breed groups with the exception of F1 Normande x Zebu (165.7 kg) and red Holstein x Zebu (165.5 kg). The Costeño con Cuernos breed had the lightest weaning weight (127.5 kg). At 18 months the Zebu breed with 249.2 kg was excelled by all the crosses, again the F1 Red Holstein x Zebu (307.5 kg) and the Normande x Zebu (295.9 kg) were the best breed groups. The Costeno con Cuernos breed with 224.6 kg held the last position. For pre and pos-weaning weight gains it was observed something similar that at weaning and 18 months. For pre-weaning gain, with the exception of F1 Normande x Zebu (0.556 kg) and Red Holstein x Zebu (0.553 kg), the Zebu breed with 0.533 kg excelled all other groups. The Costeño con Cuernos breed (0.407 kg) had the smallest pre-weaning gain. For pos-weaning gain it was observed that with the exception of the Costeño con Cuernos (0.314 kg) all other groups excelled the Zebu breed (0.322 kg). Again the Red Holstein x Zebu (0.456 kg) and the Normande x Zebu (0.435 kg) were the best.